2014
DOI: 10.1007/5584_2014_75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Provinol and Its Combinations with Clinically Used Antiasthmatics on Airway Defense Mechanisms in Experimental Allergic Asthma

Abstract: Our previous studies show that provinol, a polyphenolic compound, has anti-inflammatory activity during allergic inflammation. In the present study we investigated the effects of provinol and its combinations with clinically used antiasthmatics: budesonide or theophylline on airway defense mechanisms during experimental allergic asthma. Separate groups of guinea pigs were treated during the course of 21-day ovalbumin sensitization with provinol (20 mg/kg/day, p.o.), or budesonide (1 mM by inhalation), or theop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Exposure to vaporised e-cigarette vapour had no effects on NHBE cell viability, determined by LDH assays (see online supplementary figure S3A). Ciliary beating serves as one of the main defence functions of the airways 24. Cells exposed to nicotine-containing e-cigarette vapours had significantly reduced CBF 8 hours after exposure (5.2±0.5 Hz vs 2.6±1 Hz; p=0.01; p<0.05; figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to vaporised e-cigarette vapour had no effects on NHBE cell viability, determined by LDH assays (see online supplementary figure S3A). Ciliary beating serves as one of the main defence functions of the airways 24. Cells exposed to nicotine-containing e-cigarette vapours had significantly reduced CBF 8 hours after exposure (5.2±0.5 Hz vs 2.6±1 Hz; p=0.01; p<0.05; figure 6B).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to sperm cilia, tracheal ciliary epithelium is controlled by intracellular cAMP levels. In a recent animal study was confirmed that the ciliary beat frequency in tracheal epithelial cells is significantly higher, when ovalbumin-sensitized guinea pigs were treated with systemic theophylline at the dose of 10 mg/kg/day (Kazimierováet al, 2015). This suggests direct involvement of PDE inhibition in ameliorating the impaired defense mechanisms caused by sensitization and challenging the animals with ovalbumin, used to mimic the asthma-like conditions (airway hyperresponsiveness associated with eosinophilic inflammation).…”
Section: Non-selective Pde Inhibitorsmentioning
confidence: 87%
“…As per Pennoc, sRaw is a parameter calculated from the phase shift between nasal and thoracic respiratory flows, using the HSE respiratory software PULMODYN PENNOCK. Changes in the thoracic and nasal airflow were provoked according to a method described by Kazimierová et al (Kazimierová et al, 2015). Briefly, the animals were exposed for thirty seconds to histamine aerosol at concentration 10 -6 mol/L.…”
Section: The Evaluation Of Airway Smooth Muscle Reactivity In Vivomentioning
confidence: 99%